Global onychomycosis management and the challenges of antifungal stewardship - Aditya K. Gupta; Elizabeth A. Cooper; Eckart Haneke; Shari R. Lipner; Ditte Marie L. Saunte; Chander Grover; Avner Shemer; Bianca M. Piraccini; Antonella Tosti; Roderick J. Hay (Journal of Dermatological Treatment)
Purpose Onychomycosis, in contrast to other routine superficial dermatophyte infections, is difficult to treat and poor outcomes are not unusual. Few guidelines for onychomycosis management have been published, and these vary considerably from region to region. To meet global antifungal stewardship (AFS) goals, there must be global management guidelines for clinicians to follow in their onychomycosis practice. We aimed to survey current practices for onychomycosis management across a variety of global regions and compare practices to published treatment guidelines, as well as to what degree the management practices may facilitate AFS practices.Materials and methods An informal literature review was performed to identify regional onychomycosis guidelines. An online survey of our colleagues was distributed to assess current onychomycosis management practices and challenges for comparison with associated regional guidelines. Guidelines and practices were reviewed for adherence to the general AFS principles.Results Our review of current practices shows that, despite guidelines, identification of the infecting species is often not obtained, and treatment provision does not strictly follow existing guidelines. Lack of laboratory access prevents diagnosis and antifungal susceptibility testing that can help provide targeted treatments and resistance surveillance. Better diagnostic methods are needed as a component to improve management decisions, and provide the reliable monitoring required for effective AFS. Broader clinical testing is needed to address knowledge gaps in onychomycosis therapy. Meeting these challenges must be a priority as antifungal resistance is quickly becoming a worldwide problem.Conclusions As a reservoir for resistant strains, onychomycosis represents a significant future medical/economic burden. Future onychomycosis guidelines must address the challenge of resource limitations experienced by clinicians, as well as the challenge of balancing the need for AFS principles with the specific needs of onychomycosis therapy.